2009
DOI: 10.1111/j.1365-2966.2009.15515.x
|View full text |Cite
|
Sign up to set email alerts
|

The Konkoly Blazhko Survey: is light-curve modulation a common property of RRab stars?

Abstract: A systematic survey to establish the true incidence rate of Blazhko modulation among shortperiod, fundamental-mode, Galactic field RR Lyrae stars has been carried out. The Konkoly Blazhko Survey (KBS) was initiated in 2004. Since then, more than 750 nights of observation have been devoted to this project. A sample of 30 RRab stars was extensively observed, and light-curve modulation was detected in 14 cases. The 47 per cent occurrence rate of the modulation is much larger than any previous estimate. The signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 23 publications
6
103
0
Order By: Relevance
“…Compared to incidences 5.1% (SF07) and 4.3% (Wils et al 2006), our percentage is significantly higher and roughly approximates the percentage based on precise measurements -48% ) based on Kepler data, or 47% (Jurcsik at al. 2009a), who utilized precise ground-base observations.…”
Section: Statistics Of the Blazhko Variables In The Samplementioning
confidence: 88%
“…Compared to incidences 5.1% (SF07) and 4.3% (Wils et al 2006), our percentage is significantly higher and roughly approximates the percentage based on precise measurements -48% ) based on Kepler data, or 47% (Jurcsik at al. 2009a), who utilized precise ground-base observations.…”
Section: Statistics Of the Blazhko Variables In The Samplementioning
confidence: 88%
“…Through such data, cycle-to-cycle variations can be clearly pointed out. Indeed, the Blazhko modulation of CoRoT 101128793 is one of the smallest ever observed in RR Lyrae stars (Jurcsik et al 2009b). …”
Section: Discussionmentioning
confidence: 99%
“…The lower occurrence of longer pulsation periods in the Blazhko candidate subset is in agreement with Prudil & Skarka (2017); in our case this deficit starts at ∼0.6 d. However, there is still a large overlap in the range of pulsation period in both Blazhko and nonBlazhko populations. The 20% incident rate of Blazhko effects stars in this catalogue is lower than the figures from ground-based surveys of the Galactic field: 31% found in Skarka (2014) using a sample of 321 bright stars from ASAS and SuperWASP; and 47% found by the Konkoly Blazhko Survey (Jurcsik et al 2009). It is also lower than the 39% occurrence from the space-based Kepler mission (Szabó 2014).…”
Section: Discussionmentioning
confidence: 74%
“…However, Skarka has investigated bright RRab objects from the WASP dataset (Skarka 2014) in collaboration with data from ASAS (All Sky Automated Survey; Pojmanski 1997). Jurcsik et al (2009) suggested that the proportion of RRL showing the Blazhko effect approaches 50%, with the review by Kovacs (2016) mentioning how the occurrence rate in groundbased observations do not lag far behind space-based surveys. It is therefore an important feature of pulsating stars, not present in just a few isolated cases.…”
Section: Introductionmentioning
confidence: 99%